PROFESIONALITAS GURU PENDIDIKAN AGAMA ISLAM DALAM MENINGKATKAN PRESTASI BELAJAR SISWA DI MA AL KHOIRIYAH KERPANGAN LECES PROBOLINGGO - Moh. Imam Syafi'i; Khalilurrahman; Muhammad, Devy Habibi (LPPM STAI Muhammadiyah Probolinggo, 2024)
study aims to reveal the professionalism of Muslim teachers and their influence on students' learning outcomes in MA Al-Khoiriyah schools. Using a qualitative approach, data were collected through classroom observations, teacher interviews, and document analysis. These results highlight the importance of academic background, subject mastery, and technology integration in improving the quality of education. The results also show that collaboration among teachers and support from government and schools play an important role in creating a professional learning environment. Teachers with appropriate teaching qualifications tend to provide higher quality instruction, and their overall mastery of the subject matter influences student understanding. Technology integration and innovative teaching methods were identified as key factors to increase student engagement. Moreover, cooperation and exchange of experiences among teachers is an effective way to improve teaching skills. Government and school support, including the provision of resources, training and support, has been shown to play an important role in promoting the professional development of Islamic teachers. A supportive work environment and incentives for good performance motivate teachers. The results of this study provide an in-depth understanding of the factors that influence the professionalism of Islamic teachers and their impact on the learning success of students at MA Al-Khoiriyah. Recommendations based on these findings include improving teaching skills, developing innovative teaching methods, and increasing collaboration among teachers. It is hoped that the implementation of these recommendations will positively contribute to improving the quality of Islamic religious education at madrasa level and more broadly in Indonesia.